Inter-city competition and local government debts in China: a spatial econometric analysis. Issue 4 (2nd October 2022) - Han, Yanbing; Xiong, Min; Cheng, Shaoming; Guo, Hai (David)
ABSTRACT: Debts incurred by Chinese cities have skyrocketed. Policymakers and scholars are concerned with potential default risks and political, economic, and social impacts of a possible debt default. It has also drawn attention to drivers of the rapidly increasing municipal debts. This article examines the extent to which competition among Chinese cities affected the debts they accumulated. Drawing from the literature of local government strategic interaction and fiscal competition, we hypothesised that spillover effects might exist among Chinese cities' decisions and behaviours to issue how much bonds. With access to a panel dataset of 285 cities over 2008–2016, we applied the spatial panel regression analysis to capture and gauge the spillover effects on debt accumulation of Chinese cities. Findings confirm the spillover effects among Chinese cities and support the role that inter-city competition has played in the rapid accumulation of municipal debts.